Latinx Sexual Minority Men's Access to HIV and Behavioral Health Services in South Florida During COVID-19: A Qualitative Study of Barriers, Facilitators, and Innovations. (14th January 2022) - Harkness, Audrey; Weinstein, Elliott R.; Atuluru, Pranusha; Mayo, Daniel; Vidal, Ronald; Rodríguez-Díaz, Carlos E.; Safren, Steven A.
Abstract: Despite the availability of HIV prevention and treatment tools, HIV disparities continue to affect Latinx sexual minority men (LSMM). Behavioral health concerns further exacerbate HIV disparities among LSMM. This study used rapid qualitative analysis to understand factors influencing LSMM's access to HIV and behavioral health services during coronavirus disease 2019 (COVID-19). Participants included LSMM with ( n = 10) and without HIV ( n = 10). The analysis identified 15 themes. Themes revealed that LSMM's access was disrupted by new and worsening barriers resulting from COVID-19, such as anxiety about COVID-19 exposure, confusion and disruptions to services, and new structural challenges. Other themes highlight positive changes, such as telehealth and relaxed clinic protocols, which enhanced LSMM's access to services during COVID-19. The findings suggest the need for HIV and behavioral health clinics to innovate and ensure LSMM's continued access to services during and beyond COVID-19.